Queen Victoria's Last Laureate—and After?. (23rd September 2021) - O'Gorman, Francis
Abstract: The work of the final Poet Laureate of the Victorian period, Alfred Austin (1835–1913), has not survived among readers of poetry or drama. This essay is not an argument for that work's merits, but it does claim that we miss an important local episode of literary history, involving valuable questions about literary periodization, in the years before the establishment of Modernist poetics, if we overlook not Austin but the debates in the 1890s concerning him. Concentrating on the newspapers, periodicals, and journals of this decade, my essay discusses critics' sense that British poetry had lost its way and their implicit aspiration for new directions. The essay considers what negative models of a poet the 1890s developed, and examines critics' doubts about poetry that made direct and apparently personally sincere statements on politics in the public domain. The conclusion suggests that, while the most familiar argument is that the Modernists were turning against the 'traditional' poetry of the Victorians, the case of the reception of Alfred Austin hints at a way in which some Modernists were, without realizing it, heeding the essential advice of the last of the Victorian critics and responding to their hopes.